CRIMINAL NEGLIGENCE BY DOCTORS-A SCENARIO OF AGGRESSIVE PATIENTS, CONFUSED DOCTORS AND DIVIDED JUDICIARY! (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
The word “negligence” is always damaging to the reputation of doctors, related to some damage to the patient and a challenge  before the judges. In recent years, sudden spurt in the cases of “Criminal negligence” and decision of the Supreme Court (Dr.  Suresh Gupta vs. Govt. of NCT of Delhi) raises a fresh debate.  This paper deals with current scenario of “Criminal Negligence”, applicability of Section 304 & 304-A IPC in cases of death of patient during treatment, remedial measures available to a doctor facing the charge of ‘Criminal Negligence’ and a brief discussion  of important cases related to the issue, including recent case.
Keywords: Criminal; Doctor; Judiciary; Negligence; Patient